The effect of using distance learning in developing the technological skills of public schools' teachers in the Directorate of Education of the Kasbah of Irbid District - Aljundi, Fatehi Aref Jaber (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the level of distance learning use in public schools in the directorate of education of the Kasbah of Irbid district and its impact on the technological skills of school teachers. In order to achieve the objective of the study, the descriptive analytical method was used by developing a questionnaire as a tool for collecting data included (22) items divided into two dimensions: teachers use distance learning dimension, and teachers' technological skills dimension, and it was applied to a sample of (330) teachers from the Directorate of Education and Irbid Kasbah. The results of the study showed that the level of distance learning use in public schools in Irbid came to a medium degree, and the level of technological skills of school teachers came to a medium degree. The results also showed a statistically significant effect at the significance level (α≤0.05) of distance learning on the technological skills of school teachers in public schools in the Irbid Education Directorate. In light of the results reached, the study recommended the need to improve and develop the technical infrastructure in public schools, by improving the level of communication networks (the Internet) and equipping computer laboratories with a high degree of quality, with the aim of developing the level of distance learning and technological skills for school teachers.
Keywords: Distance Education; Technological Skills; Teachers; Jordan